2020
DOI: 10.12982/cmujns.2020.0066
|View full text |Cite
|
Sign up to set email alerts
|

Unique Genetic Structure of Y-chromosomal Lineage of the Moken from the Andaman Sea of Thailand

Abstract: To investigate the genetic structure of the Y-chromosome of the Moken people living in the Andaman Sea area of Thailand, and to compare the genetic relationship between them and other groups on the mainland, as well as the islands Southeast Asia. This study analyzed 17 Y-chromosomal short tandem repeat (Y-STR) loci in 11 unrelated Moken males from Ranong Province of Thailand. The genomic DNA was extracted from buccal cells, and amplified using an AmpFℓSTR Yfiler PCR Amplification Kit. We compared Y-STR genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Previous MSY and mtDNA studies reported the presence of haplogroups frequent in SA in some Thai populations, e.g., mtDNA haplogroups W3a1b, M30 and M45 in central Thais and Mon [ 26 , 27 ] and MSY haplogroups R1a1 in Khmer, J2a in Nyahkur and J and R in Mon [ 23 ]. However, the role of sex-biased admixture related to SA ancestry in MSEA has not been studied, and moreover only a few groups from Southern Thailand have been investigated for mtDNA and MSY variation [ 5 , 28 , 29 ]. Here, we generated new data, consisting of complete mtDNA genome sequences from TK- and AN-speaking southern Thai populations, and ∼2.3 mB of MSY sequences from the southern Thai_TK.…”
Section: Introductionmentioning
confidence: 99%
“…Previous MSY and mtDNA studies reported the presence of haplogroups frequent in SA in some Thai populations, e.g., mtDNA haplogroups W3a1b, M30 and M45 in central Thais and Mon [ 26 , 27 ] and MSY haplogroups R1a1 in Khmer, J2a in Nyahkur and J and R in Mon [ 23 ]. However, the role of sex-biased admixture related to SA ancestry in MSEA has not been studied, and moreover only a few groups from Southern Thailand have been investigated for mtDNA and MSY variation [ 5 , 28 , 29 ]. Here, we generated new data, consisting of complete mtDNA genome sequences from TK- and AN-speaking southern Thai populations, and ∼2.3 mB of MSY sequences from the southern Thai_TK.…”
Section: Introductionmentioning
confidence: 99%